The Testate Lobose Amoebae (Order Arcellinida Kent, 1880) Finally Find their Home within Amoebozoa - Nikolaev, Sergey I.; Mitchell, Edward; Petrov, Nikolay B.; Berney, Cédric; Fahrni, José; Pawlowski, Jan (My University, 2005)
Testate lobose amoebae (order Arcellinida Kent, 1880) are common in all aquatic and terrestrial habitats, yet they are one of the last higher taxa of unicellular eukaryotes that has not found its place in the tree of life. The morphological approach did not allow to ascertain the evolutionary origin of the group or to prove its monophyly. To solve these challenging problems, we analyzed partial small-subunit ribosomal RNA (SSU rRNA) genes of seven testate lobose amoebae from two out of the three suborders and seven out of the 13 families belonging to the Arcellinida. Our data support the monophyly of the order and clearly establish its position among Amoebozoa, as a sister-group to the clade comprising families Amoebidae and Hartmannellidae. Complete SSU rRNA gene sequences from two species and a partial actin sequence from one species confirm this position. Our phylogenetic analyses including representatives of all sequenced lineages of lobose amoebae suggest that a rigid test appeared only once during the evolution of the Amoebozoa, and allow reinterpretation of some morphological characters used in the systematics of Arcellinida.
Keywords: testate amoebae; phylogeny; evolution; SSU rRNA gene; actin; Amoebozoa